2019
DOI: 10.33785/ijds.2019.v72i05.007
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect on sexual behaviour of Kankrej bull

Abstract: Studies on sexual behaviour as such, and the documented reports on the influence of seasons on these characteristics are scanty for Kankrej bulls. These indices could be successfully used in selection and culling of Kankrej bulls in the breeding programs. Hence, a study on sexual behaviour of Kankrej bull was carried out at the Semen Processing Unit; with the objective to study the seasonal effect on sexual behaviour traits of Kankrej bulls. The period of investigation was divided into three season viz., summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The results of the present study are in agreement with the report (Mahmood et al, 2013) in Cholistani artificially inseminated bulls (autumn-3.49±0.07, winter-3.50±0.07, dry summer-3.47±0.07 and wet summer-3.48±0.08). On the contrary, Deka et al (2019) observed the significant effect in Kankrej bulls (summer-6.70±0.18, monsoon-6.20±0.23 and winter-5.70±0.19), Solanki et al (2019) in Gir bulls (summer-The overall dismounting time (seconds) in Deoni bulls was 2.51±0.07. The finding of the present study is in agreement with the report of Reddy and Sasikala (2013) in Jersey  Sahiwal crossbred bulls (2.67±0.15).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of the present study are in agreement with the report (Mahmood et al, 2013) in Cholistani artificially inseminated bulls (autumn-3.49±0.07, winter-3.50±0.07, dry summer-3.47±0.07 and wet summer-3.48±0.08). On the contrary, Deka et al (2019) observed the significant effect in Kankrej bulls (summer-6.70±0.18, monsoon-6.20±0.23 and winter-5.70±0.19), Solanki et al (2019) in Gir bulls (summer-The overall dismounting time (seconds) in Deoni bulls was 2.51±0.07. The finding of the present study is in agreement with the report of Reddy and Sasikala (2013) in Jersey  Sahiwal crossbred bulls (2.67±0.15).…”
Section: Resultsmentioning
confidence: 79%
“…Fertility is one of the important aspects of bull's performance for preservation of its germplasm (Naha et al, 2017). The requirement for frozen semen from superior indigenous bulls is increasing rapidly in India over the recent years due to their better milk quality, adaptability to hard climate and acceptability to poor quality feed and fodders resources (Deka et al, 2019). To achieve the required target of superior frozen semen with better fertility breeding soundness evaluation of bulls is crucial, for which sexual behavior of breeding bulls must be studied (Solanki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%